Exploring housing maintenance and vacancy in Western Australia: Perceptions of crime and crime prevention through environmental design (CPTED) - Cozens, Paul; Tarca,, M. (Emerald Group Publishing Limited, 2016)
Purpose – The purpose of this paper is to investigate “image management” as an important element within the concept to the Crime prevention through environmental design (CPTED). Globally, guidance tends to focus on promoting surveillance and few studies have explored how vacant poorly maintained housing might affect perceptions of crime and CPTED. Design/methodology/approach – This paper contrasts the perceptions of 168 members of the public and 12 built environment professionals with regards to a detached property in Perth, Western Australia. Using two photographs to elicit responses (one poorly maintained and one well-maintained) respondents were asked about their perceptions of crime, and the extent to which CPTED features were perceived to be present. These results are contrasted with a site audit of the CPTED qualities visible in both images. Findings – The CPTED audit recorded significantly higher scores for the well-maintained property than for the poorly maintained dwelling. Most respondents indicated they felt less safe, perceived more crime and lower levels of CPTED in relation to the poorly maintained house. The findings provide support that there is a link between poorly maintained housing and the perceptions of CPTED, crime and the fear of crime. Originality/value – This innovative study utilised two photographic images of the same property to probe “image management”, perceptions of crime and CPTED qualities. It highlights the need to consider these issues throughout the different stages of the development process and presents idea of the “cradle to the grave” life-cycle of criminal opportunities.